The acceleration dependent validity and reliability of 10 Hz GPS - Akenhead, R.; French, D.; Thompson, K. G.; Hayes, P. R. (Journal of Science and Medicine in Sport, 2014)
Objectives: To examine the validity and inter-unit reliability of 10 Hz GPS for measuring instantaneous velocity during maximal accelerations. Design: Experimental. Methods: Two 10 Hz GPS devices secured to a sliding platform mounted on a custom built monorail were towed whilst sprinting maximally over 10 m. Displacement of GPS devices was measured using a laser sampling at 2000 Hz, from which velocity and mean acceleration were derived. Velocity data was pooled into acceleration thresholds according to mean acceleration. Agreement between laser and GPS measures of instantaneous velocity within each acceleration threshold was examined using least squares linear regression and Bland-Altman limits of agreement (LOA). Inter-unit reliability was expressed as typical error (TE) and a Pearson correlation coefficient. Results: Mean bias ± 95% LOA during accelerations of 0-0.99 m s-2 was 0.12 ± 0.27 m s-1, decreasing to -0.40 ± 0.67 m s-1 during accelerations >4 m s-2. Standard error of the estimate ±95% CI (SEE) increased from 0.12 ± 0.02 m s-1 during accelerations of 0-0.99 m s-2 to 0.32 ± 0.06 m s-1 during accelerations >4 m s-2. TE increased from 0.05 ± 0.01 to 0.12 ± 0.01 m s-1 during accelerations of 0-0.99 m s-2 and >4 m s-2 respectively. Conclusion: The validity and reliability of 10 Hz GPS for the measurement of instantaneous velocity has been shown to be inversely related to acceleration. Those using 10 Hz GPS should be aware that during accelerations of over 4 m s-2, accuracy is compromised.